Characterizing the Motor Skills in Children with Specific Language Impairment - Teenu Sanjeevan; Elina Mainela-Arnold (S. Karger AG, 2025)
Background/Aims: Specific language impairment (SLI) is characterized by deficits in language ability. However, studies have also reported motor impairments in SLI. It has been proposed that the language and motor impairments in SLI share common origins. This exploratory study compared the gross, fine, oral, and speech motor skills of children with SLI and children with typical development (TD) to determine whether children with SLI would exhibit difficulties on particular motor tasks and to inform us about the underlying cognitive deficits in SLI.
Methods: A total of 13 children with SLI (aged 8–12 years) and 14 age-matched children with TD were administered the Movement Assessment Battery for Children – Second Edition and the Verbal Motor Production Assessment for Children to examine gross and fine motor skills and oral and speech motor skills, respectively.
Results: Children with SLI scored significantly lower on gross, fine, and speech motor tasks relative to children with TD. In particular, children with SLI found movements organized into sequences and movement modifications challenging. On oral motor tasks, however, children with SLI were comparable to children with TD.
Conclusion: Impairment of the motor sequencing and adaptation processes may explain the performance of children with SLI on these tasks, which may be suggestive of a procedural memory deficit in SLI.